2015
DOI: 10.1002/oby.21081
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal muscle myotubes in severe obesity exhibit altered ubiquitin‐proteasome and autophagic/lysosomal proteolytic flux

Abstract: ObjectiveWhole-body protein metabolism is dysregulated with obesity. Our goal was to determine if activity and expression of major protein degradation pathways are compromised specifically in human skeletal muscle with obesity.MethodsWe utilized primary Human Skeletal Muscle cell (HSkM) cultures since cellular mechanisms can be studied absent of hormones and contractile activity that could independently influence metabolism. HSkM from 10 lean (BMI ≤ 26.0 kg/m2) and 8 severely obese (BMI ≥ 39.0) women were exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 40 publications
1
28
0
Order By: Relevance
“…Previous studies have shown that LPS activates the ubiquitin–proteasome pathway through TLR4 and induces catabolism both in cultured C2C12 muscle cells [19] and in rat muscle in vivo [20]. In agreement with these findings, increased ubiquitin–proteasome activity has been reported in elderly subjects [21] and in patients with metabolic endotoxemia due to diabetes mellitus [22], obesity [23], liver cirrhosis [24], and chronic kidney disease [25,26]. Damaged or degenerated myofibers are repaired or replaced through myogenesis, the process by which myoblasts fuse to form multinucleated myotubes.…”
Section: Introductionsupporting
confidence: 66%
“…Previous studies have shown that LPS activates the ubiquitin–proteasome pathway through TLR4 and induces catabolism both in cultured C2C12 muscle cells [19] and in rat muscle in vivo [20]. In agreement with these findings, increased ubiquitin–proteasome activity has been reported in elderly subjects [21] and in patients with metabolic endotoxemia due to diabetes mellitus [22], obesity [23], liver cirrhosis [24], and chronic kidney disease [25,26]. Damaged or degenerated myofibers are repaired or replaced through myogenesis, the process by which myoblasts fuse to form multinucleated myotubes.…”
Section: Introductionsupporting
confidence: 66%
“…Myotube area was quantified by analysing the amount of MHC covering the culture area using the method of Bollinger et al . (). In addition, cell lysates were assayed for markers of differentiation (MyoD (M‐318); Santa Cruz Biotechology) and myosin heavy chain content (MHC (MF20); Developmental Studies Hybridoma Bank, Iowa City, IA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…High-fat feeding was shown to induce autophagic flux in skeletal muscles-marked by an increase in LC3-II, BECLIN1 and ULK1 and a decrease in p62 level-in a mouse model of diet induced obesity and insulin resistance (22). However, under chronic lipid overload, such as in severely obese, hyperinsulnemic human subjects, autophagic flux was blunted in primary skeletal muscle myotubes, which could contribute to the insulin resistant phenotype (79). This increase in high-fat diet-induced autophagy was absent in adiponectin-deficient mice and was restored upon adiponectin reexpression.…”
Section: Regulation Of Autophagic Activity By Lipidsmentioning
confidence: 99%